(untitled) (Public Sector Economics - submission site, 2024)
This paper aims to shed some light on the issue of euro-induced inflation in the case of the Croatian euro changeover. Applying the synthetic control method, we were unable to find unambiguous and robust evidence of such an impact on the aggregate level. Focusing on a wide array of products and services, we found no impact of the euro on most price subcategories except those related to food, clothes and restaurant prices. The findings for the latter two categories seem particularly robust, surviving a battery of alternative specifications such as the generalized synthetic control and matrix completion method. Placebo tests reveal considerable ambiguity vis-à-vis the exact timing of the euro effect on prices, probably reflecting the fact that Croatia had been a highly euroized economy years before the de iure changeover.